Long-term change of the eruption activities of Sakurajima volcano, Japan, inferred from the fallout tephra deposits - Nishihara, Ayumu; Geshi, Nobuo; Naruo, Hideto (Frontiers in Earth Science, 2022)
Stratigraphic analysis of fallout tephra deposits in and around a volcano provides a framework for understanding the long-term temporal change in the volcano’s activities. Here, we reconstruct the temporal evolution of the volcanic activities of Sakurajima volcano based on the distribution and stratigraphy of the pumice fall deposits. Our field surveys, compiled geological and archeological data, and new 14C dating reveal that Sakurajima produced a total of 14.6 km3 (5.82 DRE km3) of fallout tephra deposits. Among them, the early half of the younger Kitadake stage (13 – 8 ka) produced 12.8 km3 of tephra fallout deposits. Sakurajima peaked in magma discharge during the early half of the younger Kitadake stage (2.9 km3/kyr) and then decreased rapidly toward the latter half of the younger Kitadake stage (0.067 km3/kyr). The formation of large-volume pumice fall deposits in the early half of the younger Kitadake stage, followed by the development of a thick volcanic ash layer in the latter half, indicates the eruption style shifted from explosive pumice eruptions in the early half to ash-producing Vulcanian activity in the latter half of the younger Kitadake stage, with a decreasing magma discharge rate. Thick volcanic ash deposits covered by several pumice fall deposits during the Minamidake stage also reflect a shift in activity from repeated Vulcanian explosions with lava effusions in the older Minamidake stage to predominantly pumice eruptions during the historical period, with an increasing magma discharge rate. The case study of Sakurajima presented here demonstrates that the combined analysis of the distribution, stratigraphy, and age of pumice fall layers with the lava and pyroclastic cone deposits on the volcanic edifice is a powerful tool for deciphering the growth history of complex stratovolcanoes.